Allergen immunotherapy combined with Notch pathway inhibitors improves HDM-induced allergic airway inflammation and inhibits ILC2 activation - Tong, Yu; Wang, Lei; Wang, Lingya; Song, Jingjing; Fan, Junwen; Lai, Chuqiao; Bao, Jiali; Weng, Cuiye; Wang, Yufei; Shuai, Jilong; Zhang, Hui; Zhang, Weixi (Frontiers in Immunology, 2024)
Introduction Group 2 innate lymphoid cells (ILC2s) play a crucial role in house dust mite (HDM)-induced allergic inflammation, and allergen immunotherapy (AIT) holds promise for treating the disease by reducing the frequency of ILC2s. Despite significant progress in AIT for allergic diseases, there remains a need to improve the control of allergic symptoms. Methods We investigated the synergistic effect of the Notch signaling pathway and subcutaneous immunotherapy (SCIT) in treating allergic airway inflammation in mice and their impact on the ratio of ILC2s in lung tissues. This was achieved by establishing the HDM-induced airway allergic disorders (HAAD) model and SCIT model. Additionally, we conducted in vitro investigations into the effect of the Notch signaling pathway on the secretory function of activated ILC2s using fluorescence-activated cell sorting. Furthermore, we explored the coactivation of the Notch signaling pathway with SCIT in vitro by sorting ILC2s from the lung tissues of mice after SCIT modeling. Results Previously, our group demonstrated that Notch signaling pathway inhibitors can reduce allergic airway inflammation in mice. Notch signaling induces lineage plasticity of mature ILC2s. In this study, we showed that AIT alleviates allergic airway inflammation and suppresses the frequency of ILC2s induced by HDM. Interestingly, AIT combined with a γ-secretase inhibitor (GSI), an inhibitor of the Notch signaling pathway, significantly inhibited the frequency of ILC2s, reduced airway inflammation, and suppressed Th2-type responses in a mouse model. Furthermore, lung ILC2s from HDM-challenged mice with or without AIT were treated with GSI in vitro, and we found that GSI dramatically reduced the secretion of type 2 inflammatory factors in ILC2s. Discussion These findings suggest that Notch signaling pathway inhibitors can be used as adjuvant therapy for AIT and may hold potential treatment value in the cooperative control of allergic airway inflammation during early AIT.